Personal Solar Ultraviolet Radiation Exposure of Farmworkers: Seasonal and Anatomical Differences Suggest Prevention Measures Are Required - Linde, Karlien; Wright, Caradee Yael; du Plessis, Johannes Lodewykus (Annals of work exposures and health, 2022)
Farmworkers are at risk of excess exposure to solar ultraviolet radiation (UVR) during their work activities, especially if they work in geographical areas with high ambient solar UVR levels such as in South Africa. Excess exposure to solar UVR may lead to several negative health effects such as certain cataracts and skin cancer. This study evaluated personal solar UVR exposure of a group of farmworkers to determine if they were at risk of health-related problems due to excess solar UVR exposure. Polysulphone film (PSF) badges were placed on the shoulder, arm, and top of the head of outdoor and indoor farmworkers on a macadamia nut and avocado farm in the Limpopo province for the duration of their daily work shift to evaluate their total daily solar UVR exposure. Sixteen days were assessed for each of the three, high solar UVR seasons, i.e. autumn, spring, and summer. During autumn, farmworkers' arms received the highest solar UVR exposures (geometric mean (GM) = 7.8 SED, where 1 standard erythemal dose (SED) = 100 J/m2, 95% CI 6.1-9.8 SED) while the highest exposures were on the top of the head during spring (GM = 11.6 SED, 95% CI 7.3-17.4 SED) and summer (GM = 13.9, 95% CI 10.4-17.9 SED). Statistically significant differences in solar UVR exposure were found between the body sites during spring and summer but not autumn. The relatively high daily solar UVR exposure levels of farmworkers suggest this occupational group is at risk of excess solar UVR exposure and preventive measures with awareness information to safeguard health is necessary for employers and employees.